SETS (Science, Environment, Technology, and Society) Based Disaster Learning on Elementary School Students' Disaster Literacy and Resilience - Ruswanto; Atmojo, Setyo Eko (Universitas Pendidikan Ganesha, 2023)
This research is motivated by students' literacy and resilience to disasters, which are still relatively low. This study aims to analyze the impact of the SETS-based disaster learning model on disaster literacy and resilience of grade V elementary school students. The method used in this research is a quasi-experiment with a non-equivalent control group design. Literacy and resilience were collected by giving fifth-grade elementary school students questionnaires. The subjects involved consisted of 2 experimental classes totaling 74 students and 2 control classes totaling 88 students. The data collection technique used the questionnaire method, with the instrument tested for validation and instrument reliability. The data collection is the questionnaire method, with instruments tested for validation and reliability. Data analysis techniques used descriptive analysis tests, normality tests, homogeneity tests, and hypothesis testing, namely, the multivariate analysis of variance (Manova). The results showed that there was a significant difference in disaster literacy and resilience between students who studied using the SETS-based disaster learning model and students who studied with conventional learning models, so it can be concluded that the SETS-based disaster learning model has a positive impact on disaster literacy and resilience of grade fifth elementary school students.